Editorial - Augustine, Christine (Malaysian Journal of Music, 2022)
The Malaysian Journal of Music, Volume 11, Issue 1, comprises nine articles that present current issues in performance, musicology, music technology, practice-based research, and ethnomusicology from Thailand, Malaysia, China, and Indonesia.